Student's Discipline in Biology Online Learning in SMA Negeri 1 Sindang - Nabilah S Bajri; Hilda Oktaviani; Lesy Luzyawati; Listia Eka; Inna Nurfebriani (Jurnal Report of Biological Education, 2021)
Background: In online learning, students are required to have adequate smartphones and the internet, so that many obstacles occur, one of which concerns student discipline, especially in attendance and collection of assignments. The purpose of this study was to determine the discipline of students in online learning that took place at SMA Negeri 1 Sindang Indramayu in biology subjects. Method: The research method used is descriptive qualitative. The subjects of this study were 36 students of class XI Mipa 5 SMA Negeri 1 Sindang. The instruments used were in the form of a daily note sheet and an observation sheet. The data analysis technique used is descriptive qualitative analysis. Results: The results showed that the level of student discipline was high, as seen from the percentage of student attendance on time of 81% and the percentage of student assignment collection on time of 65%. Conclusion: The discipline of students XI mipa 5 in SMA Negeri 1 Sindang during online learning is high